A subset of microRNAs in the Dlk1‐Dio3 cluster regulates age‐associated muscle atrophy by targeting Atrogin‐1. Issue 5 (3rd June 2020) - Shin, Yeo Jin; Kwon, Eun‐Soo; Lee, Seung‐Min; Kim, Seon‐Kyu; Min, Kyung‐Won; Lim, Jae‐Young; Lee, Bora; Kang, Jae Sook; Kwak, Ju Yeon; Son, Young Hoon; Choi, Jeong Yi; Yang, Yong Ryul; et al.
Abstract: Background: The microRNAs (miRNAs) down‐regulated in aged mouse skeletal muscle were mainly clustered within the delta‐like homologue 1 and the type III iodothyronine deiodinase ( Dlk1‐Dio3 ) genomic region. Although clustered miRNAs are coexpressed and regulate multiple targets in a specific signalling pathway, the function of miRNAs in the Dlk1‐Dio3 cluster in muscle aging is largely unknown. We aimed to ascertain whether these miRNAs play a common role to regulate age‐related muscle atrophy. Methods: To examine anti‐atrophic effect of miRNAs, we individually transfected 42 miRNA mimics in fully differentiated myotubes and analysed their diameters. The luciferase reporter assay using target 3′ untranslated region (UTR) and RNA pull‐down assay were employed to ascertain the target predicted by the TargetScan algorithm. To investigate the therapeutic potential of the miRNAs in vivo, we generated adeno‐associated virus (AAV) serotype 9 expressing green fluorescent protein (GFP) (AAV9‐GFP) bearing miR‐376c‐3p and infected it into the tibialis anterior muscle of old mice. We performed morphometric analysis and measured ex vivo isometric force using a force transducer. Human gluteus maximus muscle tissues (ages ranging from 25 to 80 years) were used to investigate expression levels of the conserved miRNAs in the Dlk1‐Dio3 cluster. Results: We found that the majority of miRNAs (33 out of 42 tested) in the cluster induced anti‐atrophic phenotypes in fully differentiated myotubes with increasing their diameters. Eighteen of these miRNAs, eight of which are conserved in humans, harboured predicted binding sites in the 3′ UTR of muscle atrophy gene‐1 ( Atrogin‐1 ) encoding a muscle‐specific E3 ligase. Direct interactions were identified between these miRNAs and the 3′ UTR of Atrogin‐1, leading to repression of Atrogin‐1 and thereby induction of eIF3f protein content, in both human and mouse skeletal muscle cells. Intramuscular delivery of AAV9 expressing miR‐376c‐3p, one of the most effective miRNAs in myotube thickening, dramatically ameliorated skeletal muscle atrophy and improved muscle function, including isometric force, twitch force, and fatigue resistance in old mice. Consistent with our findings in mice, the expression of miRNAs in the cluster was significantly down‐regulated in human muscle from individuals > 50 years old. Conclusions: Our study suggests that genetic intervention using a muscle‐directed miRNA delivery system has therapeutic efficacy in preventing Atrogin‐1‐mediated muscle atrophy in sarcopenia.